2018
DOI: 10.1038/s41433-018-0131-2
|View full text |Cite
|
Sign up to set email alerts
|

Three-year incidence of Nd:YAG capsulotomy and posterior capsule opacification and its relationship to monofocal acrylic IOL biomaterial: a UK Real World Evidence study

Abstract: PurposeTo evaluate 3-year incidence of Nd:YAG capsulotomy and PCO and compare the effect of different IOL materials.MethodsData were retrospectively collected from seven UK ophthalmology clinics using Medisoft electronic medical records. Eyes from patients ≥65 years undergoing cataract surgery with implantation of acrylic monofocal IOLs during 2010–2013 and 3-year follow-up were analysed. Nd:YAG capsulotomy and PCO incidence proportions were reported for 3 IOL cohorts: AcrySof, other hydrophobic and hydrophili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 28 publications
(30 reference statements)
8
51
2
5
Order By: Relevance
“…In comparison to other currently available IOL models, the AcrySof model has shown a low incidence of PCO in many thousand eyes in several population based studies and meta-analyses [5,20]. Our study and other aforementioned, previous studies have shown a comparable performance of the Clareon and the Acry-Sof.…”
Section: Discussionsupporting
confidence: 63%
“…In comparison to other currently available IOL models, the AcrySof model has shown a low incidence of PCO in many thousand eyes in several population based studies and meta-analyses [5,20]. Our study and other aforementioned, previous studies have shown a comparable performance of the Clareon and the Acry-Sof.…”
Section: Discussionsupporting
confidence: 63%
“…А также мультицентровое ретроспективное когортное исследование P. Ursell и соавт. [14], в рамках которого проводили оценку частоты проведения Nd:YAG-лазерной капсулотомии для лечения развившейся вторичной катаракты после ФЭК с последующей имплантацией ИОЛ в течение первых 3 лет после операции.…”
Section: материалы и методыunclassified
“…В крупном ретроспективном когортном исследовании P. Ursell и соавт. [14] проводили оценку возникновения вторичной катаракты после имплантации монофокальных ИОЛ различных производителей и частоты проведения по этому поводу Nd:YAGлазерной капсулотомии. Было выявлено, что при имплантации моноблочных монофокальных ИОЛ в течение 3 лет после проведения операции частота проведения Nd:YAGлазерной капсулотомии по поводу вторичной катаракты составила 2,4 % при имплантации гидрофобных ИОЛ на платформе AcrySof®, 5,1 % -при имплантации гидрофобных ИОЛ других производителей, 10,9 % -при имплантации гидрофильных ИОЛ различных производителей.…”
Section: материалы и методыunclassified
See 1 more Smart Citation
“…Schaumberg et al [2] showed that the incidences of PCO at 1, 3, and 5 years after cataract surgery are 11.8%, 20.7%, and 28.4%, respectively. Ursell et al [3] followed up 13,329 eyes implanted with AcrySof IOL, 19,025 eyes implanted with non-AcrySof hydrophobic IOL, and 19,808 eyes implanted with non-AcrySof hydrophilic IOL for 3 years and found a 3year incidence of PCO and Nd:YAG capsulotomy ranging from 4.7% to 14.8% according to the different IOL materials used. Ambroz et al [4] found PCO in 30.9% of the surveyed eyes at 18.4-50.2 months after pediatric cataract surgery.…”
Section: Introductionmentioning
confidence: 99%